The Travelogue as a Mirror of Thought - Hamans, Camiel (Werkwinkel, 2018)
This paper discusses Dutch historical travelogues as a source for linguistic research. On the one hand one can find descriptions of exotic languages or undocumented remote dialects in travel journals, on the other hand one may come across philosophical and theoretical ideas about language in the utopian reports of imaginary voyages.